(untitled) (BIOM - Revue scientifique pour la biodiversité du Massif central, 2025)
A new plant association, Sagino procumbentis-Pedicularietum verticillatae ass. nov., is described in the Cantal mountains and in volcanic Auvergne (Massif central, France). This is a rhéophilic community of subalpine seeping cliff on volcanic tuffs, which is linked to the class of spring vegetation of Montio fontanae-Cardaminetea amarae Braun-Blanq. et Tüxen ex Klika et Hadač 1944. Vegetation surveys, including bryophytes, are analyzed to compare them to nearby communities already existing in the Cantal mountains, wet cliffs (Micranthetum hieraciifoliae Quézel et Rioux 1954) and peaty seeps (Bartsio alpinae-Caricetum nigrae J. et M.Bartsch 1940) with which the association shows floristic resemblances. It is then compared to other spring communities described in the Massif central and in France. It is characterized by a very specialized biotope, cold, longuely snow-covered, oligotrophic, with a humid Atlantic climate and very clearly neutral to basic, the latter character being remarkable in a context of siliceous volcanic bedrocks. It is an European natural priority habitat type (Natura 2000 code: 7220*). This vegetation is of great biological interest because it acts as a refuge area for numerous subalpine/alpine taxa and is home to several protected or rare species. Its original floristic composition also reflects a high biogeographic significance, as an alpine enclave located in the subalpine level of the Auvergne mountains.